Ideological Ambivalence: A Social Semiotic Multimodal Analysis of LGBT Activism in @WhatIsUpIndonesia - Elda Nisya Auliainsani; Harwintha Yuhria Anjarningsih (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
Many people have attempted to criminalize the LGBT community. This study aims to examine how @WhatIsUpIndonesia negotiates the supported ideology with the dominant ideology in their Instagram posts about criminalizing LGBT people through two different cases; the proposed revision of Indonesia's Criminal Code (RKUHP) and Bogor’s Regional Regulation on the Prevention and Countermeasures Against Sexually Deviant Behavior. A corpus of two posts about the two cases is analyzed using social semiotic multimodal analysis in two steps: textual analysis and visual analysis. This study finds that WIUI negotiates its relatively liberal values with the dominant conservative ideology in Indonesia by choosing ambivalence through the shifting focus and overgeneralizing the issue using recontextualization and memes. In conclusion, two opposing ideologies in social media activism can be negotiated using ambivalence instead of leaning towards only one. However, the limitations of this research prevented a thorough examination of how WIUI interacts with its audience.